2023
DOI: 10.1186/s40635-023-00529-z
|View full text |Cite
|
Sign up to set email alerts
|

Inferior vena cava distensibility from subcostal and trans-hepatic imaging using both M-mode or artificial intelligence: a prospective study on mechanically ventilated patients

Abstract: Background Variation of inferior vena cava (IVC) is used to predict fluid-responsiveness, but the IVC visualization with standard sagittal approach (SC, subcostal) cannot be always achieved. In such cases, coronal trans-hepatic (TH) window may offer an alternative, but the interchangeability of IVC measurements in SC and TH is not fully established. Furthermore, artificial intelligence (AI) with automated border detection may be of clinical value but it needs validation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Fluid resuscitation is the initial step in relieving circulatory disturbances in patients with DKA. However, excessive fluid resuscitation can exacerbate cerebral oedema, thus titration of fluid resuscitation is crucial [ 16 , 17 ]. Additionally, hypertonic therapy helps in transferring intracranial water into the bloodstream, ameliorating cerebral oedema with minimal impact on neurological outcomes [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fluid resuscitation is the initial step in relieving circulatory disturbances in patients with DKA. However, excessive fluid resuscitation can exacerbate cerebral oedema, thus titration of fluid resuscitation is crucial [ 16 , 17 ]. Additionally, hypertonic therapy helps in transferring intracranial water into the bloodstream, ameliorating cerebral oedema with minimal impact on neurological outcomes [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the SSC Guidelines recommend a multifaceted strategy in which the initial resuscitation phase is succeeded by a more tailored approach, incorporating dynamic indices to optimize fluid therapy and to guide further fluid therapy in patients with sepsis or septic shock. Dynamic parameters, as emphasized by the relevant literature, include response to a passive leg raise [ 31 ], a fluid bolus [ 32 ], and the utilization of various hemodynamic measures such as stroke volume, stroke volume variation, pulse pressure variation [ 33 ], and echocardiography [ 34 ] where feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Hypovolemic patients can be treated with fluid challenge therapy to increase cardiac output and optimize systemic tissue perfusion [ 37 ]. Studies have shown that the use of artificial intelligence to assess inferior vena cava variations from subcostal and trans-hepatic imaging can be used to predict fluid responsiveness [ 38 , 39 ]. We will address this shortcoming and improve it in future studies.…”
Section: Discussionmentioning
confidence: 99%